Mobile technology offers novel insights into the control and treatment of allergic rhinitis: The MASK study - Bedard, Annabelle; Klimek, Ludger (The journal of allergy and clinical immunology, 2019)
Background: Mobile health can be used to generate innovative insights into optimizing treatment to improve allergic rhinitis (AR) control. Objectives: A cross-sectional real-world observational study was undertaken in 22 countries to complement a pilot study and provide novel information on medication use, disease control, and work productivity in the everyday life of patients with AR. Methods: A mobile phone app (Allergy Diary, which is freely available on Google Play and Apple stores) was used to collect the data of daily visual analogue scale (VAS) scores for (1) overall allergic symptoms; (2) nasal, ocular, and asthma symptoms; (3) work; and (4) medication use by using a treatment scroll list including all allergy medications (prescribed and over-the-counter) customized for 22 countries. The 4 most common intranasal medications containing intranasal corticosteroids and 8 oral H-1-antihistamines were studied. Results: Nine thousand one hundred twenty-two users filled in 112,054 days of VASs in 2016 and 2017. Assessment of days was informative. Control of days with rhinitis differed between no (best control), single (good control for intranasal corticosteroid-treated days), or multiple (worst control) treatments. Users with the worst control increased the range of treatments being used. The same trend was found for asthma, eye symptoms, and work productivity. Differences between oral H-1-antihistamines were found. Conclusions: This study confirms the usefulness of the Allergy Diary in accessing and assessing behavior in patients with AR. This observational study using a very simple assessment tool (VAS) on a mobile phone had the potential to answer questions previously thought infeasible.
Gesehen am 03.09.2019